Research on Biological Detection Based on Reflected Light Images of a Porous Silicon Bragg Mirror - Shuangshuang Zhang; Miao Sun; Jianfeng Yang; Zhenhong Jia; Xiaoyi Lv; Xiaohui Huang (IEEE Photonics Journal)
In this paper, based on the gray value change of reflected light image of porous silicon (PSi) Bragg mirror, a fast and simple biological detection method is proposed. In this method, CdSe/ZnS quantum dots (QDs) are used as markers for refractive index amplification, and digital image method is used for detection. The detection light has the same wavelength as the lowest reflectivity of the edge of the Bragg mirror, and the reflected light radiated on the surface of the Bragg mirror is received by the detector. The theoretical simulation results show that the intensity of the reflected light increases with the increase of the refractive index caused by the biological reaction. According to the experimental results, the average gray value variation increases with the increase of the target DNA concentration and becomes a linear relationship in a certain range. Based on this method, the DNA detection limit is 20.74 pM. The method is low-cost, has a short detection time and can be used in the detection of biosensor microarray.